Pengembangan Model Kemitraan Sekolah Dasar Berbasis Partisipasi Aktif: Studi Literatur - Dwi Indah Lestari; Rizky Zulfa Amelia; Rizka Amelia; Siti Mahdalena Zahra; Syahida Nabila Arrifa; Nameira Melati Puteri; Suhaimi Suhaimi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
School–community partnerships are a strategic pillar in improving the quality of elementary education in Indonesia. However, the reality in the field shows that community participation in educational management remains relatively low and tends to be passive. This study aims to examine and develop the concept of an elementary school partnership model based on active participation through a literature review approach. This research employs a qualitative approach using a literature review method by analyzing various scientific journals related to active participation in elementary school partnerships. The results of the review indicate that effective elementary school partnerships are built through several key components, namely open and continuous communication between schools and the community, parental involvement in the learning process and decision-making, collaboration with community institutions and the business sector, and strengthening the role of the community in supporting educational activities.